Association between urinary community-acquired fluoroquinolone-resistant Escherichia coli and neighbourhood antibiotic consumption: a population-based case-control study. Issue 4 (April 2019) - Low, Marcelo; Neuberger, Ami; Hooton, Thomas M; Green, Manfred S; Raz, Raul; Balicer, Ran D; Almog, Ronit
Summary: Background: It is unknown whether increased use of antibiotics in a community increases the risk of acquiring antibiotic resistance by individuals living in that community, regardless of prior individual antibiotic consumption and other risk factors for antibiotic resistance. Methods: We used a hierarchical multivariate logistic regression approach to evaluate the association between neighbourhood fluoroquinolone consumption and individual risk of colonisation or infection of the urinary tract with fluoroquinolone-resistant Escherichia coli . We did a population-based case-control study of adults (aged ≥22 years) living in 1733 predefined geographical statistical areas (neighbourhoods) in Israel. A multilevel study design was used to analyse data derived from electronic medical records of patients enrolled in the Clalit state-mandated health service. Findings: 300 105 events with E coli growth and 1 899 168 cultures with no growth were identified from medical records and included in the analysis. 45 427 (16·8%) of 270 190 women and 8835 (29·5%) of 29 915 men had fluoroquinolone-resistant E coli events. We found an independent association between residence in a neighbourhood with higher antibiotic consumption and an increased risk of bacteriuria caused by fluoroquinolone-resistant E coli . Odds ratios (ORs) for the quintiles with higher neighbourhood consumption (compared with the lowest quintile) were 1·15 (95% CI 1·06–1·24), 1·31 (1·20–1·43), 1·41 (1·29–1·54), and 1·51 (1·38–1·65) for women, and 1·17 (1·02–1·35), 1·24 (1·06–1·45), 1·35 (1·15–1·59), and 1·50 (1·26–1·77) for men. Results remained significant when the analysis was restricted to patients who had not consumed fluoroquinolones themselves. Interpretation: These data suggest that increased use of antibiotics in specific geographical areas is associated with an increased personal risk of acquiring antibiotic-resistant bacteria, independent of personal history of antibiotic consumption and other known risk factors for antimicrobial resistance. Funding: None.